Implementation of directed activities of physical education through dramatization of the cartoon "the smurfs" in preschool children - Stanišić, Irena R; Ranđelović, Nebojša M (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2018)
Besides the usual guided activities in physical education of preschool children based on applying certain forms of movements, performing certain tasks and aquiring mobile games, activities on a particular topic can also be succsessfuly organized. The aim of this work and these targeted actions is the elaboration of specific contents based on selected themes from the cartoon "The Smurfs", which are adjusted to the goal that forms the basic units of activity - prevention of flat feet. These contents have a goal to arouse children's imagination, to enable children to play and develop creativity, master certain forms of movements and develop orientation in time and space. This activity has a significant impact on strengthening the muscles of the arms, shoulders and legs and development of overall motor skills and socialization of children and can be used in all age groups. It also has an important influence in the development of imagination and creativity in children, as well as non-verbal communication skills through the use of gesture and movements and it should educate through entertainment. These focused activities have significant correlations with speech developing and art education.
Keywords: CHILDREN; flat feet prevention; dramatization; focused activity; physical education